Risk of second primary malignancies among 1537 melanoma patients and risk of second primary melanoma among 52 354 cancer patients in Northern Italy. (18th March 2016) - Caini, S.; Radice, D.; Tosti, G.; Spadola, G.; Cocorocchio, E.; Ferrucci, P.F.; Testori, A.; Pennacchioli, E.; Fargnoli, M.C.; Palli, D.; Bazolli, B.; Botteri, E.; et al.
Abstract: Background: The number of melanoma survivors has been increasing for decades due to early diagnosis and improved survival. These patients have an increased risk of developing a second primary cancer (SPC); also, melanoma is frequently diagnosed among patients firstly diagnosed with an extracutaneous malignancy. Objective: We evaluated the risk of developing a SPC among 1537 melanoma patients, and the risk of second primary melanoma (SPM) in 52 354 extracutaneous cancer patients, who were treated at the European Institute of Oncology in Milan, Italy, during 2000–2010. Material and methods: We calculated standardized incidence ratios (SIR) by applying gender‐, age‐, year‐ and region‐specific reference rates to the follow‐up time accrued between the diagnosis of the first and the second primary malignancies. Results: Seventy‐six SPC were diagnosed during a median follow‐up of 4 years, of which 49 (64%) during the first 2 years upon melanoma diagnosis. The SIR was increased for cancer of breast (4.10, 95% CI 2.79–6.03), thyroid (4.67, 95% CI 1.94–11.22), brain (6.13, 95% CI 2.30–16.33) and for non‐Hodgkin lymphoma (3.12, 95% CI 1.30–7.50). During a median follow‐up of 4 years, 127 SPM were diagnosed: thick lesions were less frequent than for melanoma diagnosed as first cancer. The SIR was increased for cancer of breast (5.13, 95%CI 3.91–6.73), thyroid (16.2, 95%CI: 5.22–50.2), head and neck (5.62, 95%CI 1.41–22.50), soft tissue (8.68, 95%CI 2.17–34.70), cervix (12.5, 95% CI 3.14–50.20), kidney (3.19, 95%CI 1.52–6.68), prostate (4.36, 95%CI 2.63–7.24) and acute myeloid leukaemia (6.44, 95%CI 2.42–17.20). Conclusions: The most likely causes of these associations are the clustering of lifestyle risk factors in the same subgroups of population, mainly on a sociocultural basis and surveillance bias. This raises important questions about how to best follow cancer survivors by avoiding an inefficient use of resources and an excessive medicalization of these patients' lives.